Social media and border security: Twitter use by migration policing agencies - Walsh, James P. (Policing and society, 2020)
Social media are transforming public communication and state-society relations, dynamics distinctly visible in the domains of policing and order maintenance. Despite growing research on this relationship, scholarship has adopted an internalist optic, privileging social media use by domestic law enforcement. Using an original data set, this paper broadens the scale of analysis to consider Twitter usage by federal agencies tasked with border security and migration policing in Australia, Canada, and the United States. Despite new technologies’ transformational potential, its findings suggest Twitter is overwhelmingly employed for the conventional purposes of broadcasting information, managing impressions, and enlisting public assistance. Message themes linked with greater user responsiveness are also identified. The deeper implications of these findings and directions for future research are discussed.